Virtual Dark Tourism Ghost Roads (Palgrave Studies in Cultural Heritage and Conflict, 2018)
This book takes the concept of "dark tourism"-journeys to sites of death, suffering, and calamity-in an innovative yet essential direction by applying it to the virtual realms of literature, film and television, the Internet, and gaming. Essays focus both on the creative construction of imaginary journeys and the historiographic and civic consequences of such memorializations. From World War II time-travel novels to Game of Thrones, and from Internet reproductions of Rwandan genocide locations to invented tragedies in futuristic domains, authors from various fields examine the purpose and influence of simulated travels to morbid sites. Designed for a wide audience of scholars and travelers virtual and real, this volume raises awareness about the many pathways through which we encounter death experiences in contemporary society. What we know about the past-or, what we think we know about it-is shaped daily by such imagined journeys as these. Kathryn N. McDaniel is Andrew U. Thomas Professor of History and Chair of the Department of History, Philosophy, and Religion at Marietta College, USA. A British historian specializing in intersections between popular culture and history, she is also co-editor of Harry Potter for Nerds 2.